2020
DOI: 10.1016/j.tibs.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Location, Location, Location: Compartmentalization of NAD+ Synthesis and Functions in Mammalian Cells

Abstract: The numerous biological roles of NAD + are organized and coordinated via its compartmentalization within cells. The spatial and temporal partitioning of this intermediary metabolite is intrinsic to understanding the impact of NAD + on cellular signaling and metabolism. We review evidence supporting the compartmentalization of steady-state NAD + levels in cells, as well as how the modulation of NAD + synthesis dynamically regulates signaling by controlling subcellular NAD + concentrations. We further discuss po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 131 publications
(178 reference statements)
4
93
0
Order By: Relevance
“…Both CEC and macrophage played important effects in the hyperosmolarity-induced ocular surface, however, the interaction between CEC and macrophage was still eagerly required to be investigated. NMN had been reported to be related with the incidence of a variety of chronic diseases 17 and recently reported to play a protective effect in ocular diseases. 16 In the present study, it was confirmed HS treatment would lead to an increased expression of IL-17a in CEC and thus induce the activation of macrophage based on a CEC/macrophage co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Both CEC and macrophage played important effects in the hyperosmolarity-induced ocular surface, however, the interaction between CEC and macrophage was still eagerly required to be investigated. NMN had been reported to be related with the incidence of a variety of chronic diseases 17 and recently reported to play a protective effect in ocular diseases. 16 In the present study, it was confirmed HS treatment would lead to an increased expression of IL-17a in CEC and thus induce the activation of macrophage based on a CEC/macrophage co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the liver where NAD + levels were shown to predominantly depend on tryptophan, many tissues and most transformed cell culture cell lines synthesize NAD + from NAM and thus rely mostly on the salvage pathway [ 38 ]. The salvage pathway depends on the expression level of nicotinamide phosphoribosyltransferase (NAMPT) and the nicotinamide mononucleotide adenylyl transferases (NMNATs), NMNAT1, 2 and 3 [ 42 , 43 ]. The localization of the three NMNATs is described to be enzyme-specific, with NNMAT1 localizing mainly to the nucleus, NMNAT2—to the cytoplasm as well as to the Golgi apparatus and NMNAT3—to the mitochondria [ 44 , 45 , 46 ].…”
Section: Nad + Synthesis and Its Involvement Inmentioning
confidence: 99%
“…Compartment-specific NAD homeostasis has been highlighted in recent studies as an important determinant of physiological processes such as adipocyte differentiation, neuronal cell survival, metabolic regulation of transcription, and electron transport chain activity [39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%